Simulasi Aplikasi Posyandu Berdasarkan Konsep RFID (Radio Frequency Identification) - Eridani, Dania; Widianto, Eko Didik (Jurnal Sistem Komputer, 2014)
This paper discuss the development of posyandu application to facilitate posyandu officer in handling the administration process based on RFID concept. The main idea is making the health card function as one unique identity like the unique number in RFID and it will contain all user data and activity in posyandu. The data used in this application are mostly for children data like immunization, vitamin distribution, and height and weight measurement. All data used in this application is saved to local database in each computer used by the posyandu officer.